ANTIOXIDANT ACTIVITY OF THE COMBINATION OF AMBARELLA LEAVES (Spondias dulcis Parkinson) AND SOURSOP LEAVES (Annona muricata Linn) EXTRACT - Tarso Rudiana; Dimas Danang Indriatmoko; Ken Virginia (Universitas Muhammadiyah Magelang, 2023)
Degenerative diseases can be caused by free radicals, whereas antioxidants can overcome free radicals. Kedondong leaves (Spondias dulcis Parkinson) and soursop leaves (Annona muricata Linn.) are potential sources of suitable antioxidant compounds. This study aims to determine the antioxidant activity and the relationship between antioxidants and total phenolics from the combination of S. dulcis and A. muricata leaf extracts. S. dulcis leaves, and A. muricata leaves were macerated with 96% ethanol and then formulated with a combination of extracts (1:1, 2:1, and 1:2). Each was tested for its antioxidant activity by the DPPH method. The ethanol extract of S. dulcis leaves had an antioxidant activity value of 36.72±4.01 ppm with a total phenol of 76.84±0.50 mgGAE/g extract, an ethanol extract of A. muricata leaves of 81.45±8.19 ppm with a total phenol of 104.48±7.55 mg GAE/g extract and a combination of extracts with a ratio of ethanol extract of S. dulcis leaves and ethanol extract of A. muricata leaves (2:1) of 29.98 ± 0.37 ppm with a total phenol of 36.99 ± 0.98 mgGAE/g extract. The results showed that the phenolic content of the ethanol extract of A. muricata leaves was more significant than the combination (2:1), which had the most excellent antioxidant activity among the other comparisons. Total phenolic is inversely related to antioxidant activity. Antioxidant activity is not only played by phenolic compounds.